Hegel: Beyond good and evil? - Cubo Ugarte, Óscar (Estudios de Filosofía, 2008)
With the title of our work we pretend is to research on the problem of Liberty in the figure of G. W. F. Hegel from an Ontological Perspective. With this aim in view, we have wanted to separate the Moral Problem of Liberty from its own Ontological Dimension, especially in the text: The Phenomenology of the Spirit (that in our days completes its two hundredth Anniversary of publication). Through this analysis of the problem of Liberty in the Phenomenology of the Spirit, we have also achieved to bring to light the profound familiarity of Hegelian thought with other currents thought which are radically genealogist and immoralist, such as Nietzsche’s and Spinoza’s.